DEVELOPMENT OF MANUAL WORK IN PRE-SCHOOL EDUCATION - Karimova Shoira Bakhtiyarovna (Galaxy International Interdisciplinary Research Journal, 2024)
Labor education of preschool children cannot be imagined without active manual labor. In this type of activity, the child feels high interest. This factor has a positive effect on the general mental development of children. The article describes the benefits of manual labor for children of kindergarten age and the aspects required from pedagogues.